2013
DOI: 10.1002/jpln.201200257
|View full text |Cite
|
Sign up to set email alerts
|

Potassium‐fertilizer management in winter oilseed‐rape production in China

Abstract: Optimal potassium (K) fertilization is beneficial for oilseed-rape (Brassica napus L.) yield and quality. However, the discrepancy between the high K demand of winter oilseed rape and low soil fertility and insufficient potassium input has limited the sustainable development of oilseedrape production. A series of on-farm experiments in the key winter oilseed-rape domains of China was conducted from 2004 to 2010 to evaluate K-fertilizer management for winter oilseed rape. Currently, the average NH 4 OAc-extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…But the relationship between soil NH 4 OAc-K content and relative yield was weak in our study because of minor response to K fertilization. The average yield increase rate associating with K fertilization was 11.5%, similar to that reported by Ren et al (2013). The relationship between plantavailable soil K supply, seed yield of the 0-K treatment and relative yield was also poor.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…But the relationship between soil NH 4 OAc-K content and relative yield was weak in our study because of minor response to K fertilization. The average yield increase rate associating with K fertilization was 11.5%, similar to that reported by Ren et al (2013). The relationship between plantavailable soil K supply, seed yield of the 0-K treatment and relative yield was also poor.…”
Section: Discussionsupporting
confidence: 85%
“…In 2013, more than 36.4 million hectares of lands were devoted to growing oilseed rape with a production of 59,172.5 million tons (FAOSTAT 2014). The use of mineral fertilizer plays an important role in achieving high seed yields (Sieling and Kage 2010;Ren et al 2013). Many experiments on the fertilization of field and potted oilseed rape have been showed that the optimal N application rates range from 90 to 200 kg N ha −1 (Fismes et al 2000;Cheema et al 2001;Ozer 2003;Rathke et al 2005;Malhi et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The negative impact of K deficiency on photosynthesis, transpiration and stomatal conductance is well documented . Potassium deficiency symptoms may not necessarily be readily visible or observed in the field owing to a rapid reallocation of K within the plant, so the fundamental importance of K may not be directly appreciated . The content of chlorophylls (Chl b and total Chl) was not affected by either of the K levels used in this study (375 or 125 mg L −1 ) or by SW application (Table ).…”
Section: Discussionmentioning
confidence: 79%
“…The location of potassium loss in biotite determines the release pattern of potassium in two ways including (1) exchange interaction, H + or Na + cation exchanges K + from the edge of the (h k 0) and interlayer via kinks or defect sites on the biotite (0 0 1) surface, which will not lead to evident alteration on a biotite structure (Hu et al, 2011); (2) hydrolysis, H + reacts with Al-O-Al and Si-O-Si to break the lattice charge-balancing and release K + , which will destroy the mica crystal structure (Ganor et al, 2009;Munson, 1985). Biotite has abundant K, which is one of the three most essential nutrients for plants (Ren et al, 2013;Samal et al, 2010;Steingrobe and Claassen, 2000). Where K deficiency is common, such as in China, India, Sri Lanka and regions of Southeast Asia (Li et al, 2009;Pathak et al, 2009), biotite breakdown is very important for improving available K in soils (Manning, 2010 Previous studies suggest that mica dissolution rates vary as a function of pH much as they did in other aluminosilicates.…”
Section: Introductionmentioning
confidence: 98%